2014
DOI: 10.1017/s0030605314000258
|View full text |Cite
|
Sign up to set email alerts
|

Occupancy and abundance of large macaws in the Beni savannahs, Bolivia

Abstract: Monitoring of wild populations is central to species conservation and can pose a number of challenges. To identify trends in populations of parrots, monitoring programmes that explicitly take detectability into account are needed. We assessed an occupancy model that explicitly accounted for detectability as a tool for monitoring the large macaws of Bolivia's Beni savannahs: the blue-throated Ara glaucogularis, blue-and-yellow Ara ararauna and red-and-green macaws Ara chloropterus. We also evaluated the joint p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 20 publications
(37 reference statements)
0
18
1
2
Order By: Relevance
“…However, in our work, we were able to measure these effects and confirm the direct relationship between hunting and selective logging with village distance. Berkunsky et al (2014) proposed that this variable can be used to predict the range of spatial distribution of parrot species that are affected by human presence in the savannah of Beni, Bolivia. Considering this, it could be used as a key tool to identify important areas for the conservation of persecuted species, such as cracids.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our work, we were able to measure these effects and confirm the direct relationship between hunting and selective logging with village distance. Berkunsky et al (2014) proposed that this variable can be used to predict the range of spatial distribution of parrot species that are affected by human presence in the savannah of Beni, Bolivia. Considering this, it could be used as a key tool to identify important areas for the conservation of persecuted species, such as cracids.…”
Section: Discussionmentioning
confidence: 99%
“…Riverine gallery forest borders rivers on raised fluvial deposits (Lombardo, 2014) and forest islands are small (<50 m width), round-shaped patches of trees on elevated areas in a treeless savanna landscape, formed by anthropogenic influences or termite mounds (Denevan, 1966;Erickson, 1995;Lombardo et al, 2013). These patches are modified by environmental drivers such as human-induced and natural fires in the dry season, and inundation in the wet season (Berkunsky et al, 2016).…”
mentioning
confidence: 99%
“…For the past 12,000 years, the Beni savanna has been influenced by human activity (Erickson, 2000;Haase & Beck, 1989;Lombardo et al, 2013;Navarro & Maldonado, 2002) as the savanna was inhabited by a dense population of pre-Columbian Paleo-Indians who constructed earth mounds for agriculture and habitation, and dug canals and fishing ponds (Denevan, 1966;Erickson, 2000). Nowadays, the main human impacts are protracted and uncontrolled cattle grazing, burning of savanna by farmers to ensure fresh grass sprout for cattle, natural grassland conversion, and forest destruction for cattle ranching infrastructure (Berkunsky et al, 2016;Killeen, 1991;Killeen et al, 2003;Mayle et al, 2007).…”
mentioning
confidence: 99%
“…Population viability analyses suggest that further or even small annual increases in habitat loss (2%) and trapping (3%) would significantly increase its extinction risk over the next 50 years (Bouzat and Strem 2012). The habitat loss hypothesis is challenged by our SDMs, which show the current extent of suitable habitat for the species could currently hold a much larger, healthier population; in fact, congeneric macaws are present in the same region at high densities (Berkunsky et al 2015, 2016). Regarding the wild-bird trade hypothesis, trade in the most attractive parrot species (including macaws) has been related to their population decline and current threatened status (Tella and Hiraldo 2014).…”
Section: Discussionmentioning
confidence: 96%
“…Carrete et al 2009, Cardador et al 2016, Ferrer-Sánchez and Rodríguez-Estrella 2016). For this species, all known breeding sites are within private and highly managed cattle ranches, and recent occurrence models obtained at a smaller spatial scale showed that, contrary to other sympatric macaws (Blue-and-yellow Ara ararauna and Red-and-green Ara chloropterus ), the Blue-throated Macaw does not appear to avoid human settlements (Berkunsky et al 2016). This might suggest that Blue-throated Macaws prefer more human-altered areas and/or that they are displaced towards those areas by stronger congeneric competitors (see below).…”
Section: Discussionmentioning
confidence: 99%